Preparation process of charcoal essence

By constructing a molecular imprinting structure on the surface of the carbon material and combining plant fiber composite carriers, and designing a biphasic or multiphase layered storage system, the problems of low utilization rate of active ingredients, insufficient long-term sustained release and poor stability in the carbon essence liquid are solved, and more efficient utilization of active ingredients and longer-term skin care effects are achieved.

CN119564515APending Publication Date: 2025-03-07HEBEI RUIMU CARBON-BASED AGRI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411760899.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

There are problems with low utilization rate of active ingredients in existing carbon essence liquids, insufficient long-term sustained release effect and poor stability.

Method used

By constructing a molecular imprinted structure on the surface of carbon materials and combining plant fiber composite carriers, a biphasic or multiphase layered storage system is designed to ensure effective capture, slow release and stable storage of active ingredients.

Benefits of technology

It improves the utilization rate and sustained release effect of active ingredients, extends the skin care time, and enhances the stability and user experience of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564515A_ABST
    Figure CN119564515A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of skin care product preparation, and discloses a carbon essence preparation process, which comprises: S1, carbon material pretreatment: crushing a carbon material until the particle size is 10-50 nm, and carrying out surface treatment on the carbon material by using a surface modifier so as to form active sites on the surface of the carbon material; s2, preparation of a molecularly imprinted carbon material: mixing the pretreated carbon material with a template molecule, a monomer and a cross-linking agent, and carrying out a copolymerization reaction on the surface of the carbon material to form a molecularly imprinted structure; and S3, after the reaction is completed, removing the template molecules by using a washing solvent. A molecular imprinting structure is constructed on the surface of a carbon material, accurate adsorption and utilization rate improvement of active ingredients are achieved, long-acting slow release is achieved through a plant fiber composite carrier, a double-phase or multi-phase layered storage design is adopted, freshness and high efficiency of the ingredients are ensured, meanwhile, the composite carrier forms a water-locking protection layer on the skin surface, and the skin-care effect is achieved. The moisturizing effect of the product is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of skin care product preparation, in particular to a preparation process of a charcoal essence liquid. Background Art

[0002] In the field of skin care products, essence has become a popular skin care product due to its high concentration of active ingredients and excellent penetration ability. In recent years, carbon materials have been gradually introduced into skin care products due to their excellent adsorption and biocompatibility, especially in the fields of cleaning and skin care. Carbon materials can absorb impurities and oils on the surface of the skin, and their porous structure also provides favorable conditions for the carrying of active ingredients. Therefore, introducing carbon materials into essence can not only clean pores, but also effectively load active ingredients to provide deep nourishment for the skin.

[0003] However, there are still some problems in the preparation of carbon-containing essences in the prior art, mainly including low utilization of active ingredients, insufficient long-term sustained-release effect, and poor stability. The active ingredients in traditional essences are usually released quickly after application and are difficult to remain on the skin for a long time, resulting in a short duration of action of the skin care ingredients. Users need to use it frequently to maintain the effect. In addition, the dispersion stability of carbon materials in essences is also poor, and precipitation or stratification is prone to occur, affecting the user experience.

[0004] In view of the above problems, the present invention proposes a preparation process of carbon essence liquid. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a preparation process of a charcoal essence liquid, which solves the problems of low utilization rate of active ingredients, insufficient long-acting sustained release and poor stability in the prior charcoal essence liquid.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A process for preparing a carbon essence liquid comprises the following steps:

[0007] S1. Pretreatment of carbon materials: crushing the carbon materials to a particle size of 10-50 nm, and surface treating the carbon materials with a surface modifier to form active sites on the surface of the carbon materials;

[0008] S2. Preparation of molecularly imprinted carbon material: mixing the pre-treated carbon material with the template molecule, the monomer and the cross-linking agent, and performing copolymerization on the surface of the carbon material to form a molecularly imprinted structure;

[0009] S3, after the reaction is completed, the template molecules are removed using a washing solvent to obtain a molecularly imprinted carbon material;

[0010] S4. Preparation of plant fiber network structure: dissolving or dispersing plant fibers in water, and preparing a three-dimensional porous network structure by adjusting the pH value and controlling the stirring temperature and time;

[0011] S5. Preparation of plant fiber composite carrier: cross-linking the molecularly imprinted carbon material with the plant fiber network structure to obtain the plant fiber composite carrier;

[0012] S6. Preparation of active ingredients of water phase and oil phase:

[0013] Prepare an aqueous phase by dissolving sodium hyaluronate and water-soluble components of tea polyphenols in deionized water;

[0014] preparing an oil phase by uniformly mixing vitamin E and squalane-based oil-soluble components to obtain an oil phase;

[0015] S7. Design and loading of layered storage system: the plant fiber composite carrier, water phase and oil phase are sequentially loaded into the container in layers, and a double-layer diaphragm is provided in the container to isolate the components of each layer;

[0016] S8. Product sealing and storage: Seal the filled container and store it.

[0017] Preferably, the pretreatment of the carbon material in step S1 comprises mixing the carbon material with a 0.02 mol / L 3-aminopropyltriethoxysilane solution and stirring the mixture in a 60° C. water bath for 1-3 h.

[0018] Preferably, the step of preparing the molecularly imprinted carbon material in step S2 comprises:

[0019] The template molecule is vitamin C, with a concentration of 0.01-0.1 mol / L;

[0020] The monomer is methyl methacrylate, and the concentration is 0.1-0.5 mol / L;

[0021] The cross-linking agent is ethylene glycol dimethacrylate, and the concentration is 0.05-0.2 mol / L;

[0022] The polymerization reaction was carried out at 50-70°C for 2-4h under nitrogen protection.

[0023] Preferably, the step of removing the template molecules in step S3 comprises washing alternately with ethanol and deionized water assisted by ultrasonic wave, each washing lasting 5-10 minutes, for a total of three washings.

[0024] Preferably, in step S4, the plant fiber is seaweed fiber with a concentration of 0.5-2% w / v, and a porous network structure is formed by adjusting the pH of the solution to 6-7 and stirring at 30-50° C. for 0.5-2 h.

[0025] Preferably, the preparation of the plant fiber composite carrier in step S5 comprises adding the molecularly imprinted carbon material into the seaweed fiber solution, adding calcium chloride as a cross-linking agent at a concentration of 0.01-0.05 mol / L, and reacting at 20-25° C. for 20-40 min.

[0026] Preferably, the hierarchical storage system in step S7 includes a three-layer structure, namely:

[0027] The first layer is the aqueous phase, which contains sodium hyaluronate and tea polyphenols in a concentration range of 0.01-0.1% w / v;

[0028] The second layer is the oil phase, which contains vitamin E and squalane in a concentration range of 0.05-0.5% w / v;

[0029] The third layer is a carbon material / plant fiber composite phase, the carbon material concentration is 0.1-1% w / v, and the plant fiber concentration is 0.5-2% w / v.

[0030] Preferably, in step S7, the thickness of the double-layer diaphragm in the container is 0.1-0.5 mm.

[0031] Preferably, the specific steps of preparing the aqueous phase in step S6 include:

[0032] Dissolve sodium hyaluronate and tea polyphenols in deionized water, and control the initial temperature of the water at 20-30°C;

[0033] The concentration of sodium hyaluronate is 0.05-0.2% w / v, and the concentration of tea polyphenols is 0.01-0.1% w / v;

[0034] A magnetic stirrer is used during the dissolution process, with a stirring speed of 200-500 rpm and a stirring time of 15-30 min until the sodium hyaluronate is completely dissolved;

[0035] After adding tea polyphenols to the sodium hyaluronate solution, continue stirring for 5-15 minutes to make it evenly dispersed and dissolved;

[0036] The pH value of the solution can be adjusted to 5.0-6.5.

[0037] Preferably, the specific steps of preparing the oil phase in step S6 include:

[0038] In a clean container, vitamin E and squalane are uniformly mixed, wherein the concentration of vitamin E is 0.1-0.3% w / v, and the concentration of squalane is 0.05-0.2% w / v;

[0039] Use a stirrer to stir at a speed of 150-300 rpm for 15-30 min to fully dissolve the vitamin E and squalane to form a uniform oil phase;

[0040] If necessary, the temperature can be raised to 30-50°C to accelerate dissolution, and avoid light during stirring.

[0041] The present invention provides a preparation process of a carbon essence liquid, which has the following beneficial effects:

[0042] 1. The present invention constructs a specific molecular imprinting structure on the surface of the carbon material, so that the carbon material can specifically identify and adsorb skin care active ingredients, such as vitamin C, hyaluronic acid, etc. The "molecular lock" structure ensures that the active ingredients are firmly captured and fixed in the carbon material before use, thereby reducing the loss of ingredients during storage or application, improving the effective utilization rate of active ingredients, and making the skin care effect of the essence more significant.

[0043] 2. The present invention combines molecular imprinting technology with a plant fiber composite carrier to enable the charcoal essence to achieve a slow release of active ingredients. During use, the molecular imprinting structure of the carbon material has a significant sustained-release effect and can gradually release skin care ingredients to ensure that the skin is nourished for a long time after application. The sustained-release property effectively prolongs the skin care effect time of the product and avoids the problem of ingredient waste and effect attenuation caused by a one-time release.

[0044] 3. The present invention adopts a dual-phase or multi-phase layered storage design. By separating different components such as carbon materials, water phase, oil phase, etc., each active ingredient is isolated and stored to avoid mutual influence. When in use, the container is pressed, and the layered contents are instantly mixed, so that each component reaches a highly active state at the moment of use. This design maintains the freshness of the active ingredients, improves the use effect, and ensures the activity and effectiveness of the ingredients each time they are used.

[0045] 4. The charcoal essence of the present invention utilizes a composite carrier design of charcoal material and natural plant fiber to form a water-locking protective layer on the skin surface, significantly improving the long-lasting moisturizing effect of the product. The natural plant fiber not only enhances the adhesion of the charcoal material on the skin and prolongs the residence time of the skin care ingredients on the skin surface, but also slowly releases moisture and nutrients, effectively preventing moisture loss and helping the skin stay hydrated. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The present invention is a flow chart of the preparation process. DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Please see attached Figure 1 The present invention provides a process for preparing a carbon essence liquid, comprising the following steps:

[0049] S1. Pretreatment of carbon materials: crushing the carbon materials to a particle size of 10-50 nm, and surface treating the carbon materials with a surface modifier to form active sites on the surface of the carbon materials;

[0050] S2. Preparation of molecularly imprinted carbon material: mixing the pre-treated carbon material with the template molecule, the monomer and the cross-linking agent, and performing copolymerization on the surface of the carbon material to form a molecularly imprinted structure;

[0051] S3, after the reaction is completed, the template molecules are removed using a washing solvent to obtain a molecularly imprinted carbon material;

[0052] S4. Preparation of plant fiber network structure: dissolving or dispersing plant fibers in water, and preparing a three-dimensional porous network structure by adjusting the pH value and controlling the stirring temperature and time;

[0053] S5. Preparation of plant fiber composite carrier: cross-linking the molecularly imprinted carbon material with the plant fiber network structure to obtain the plant fiber composite carrier;

[0054] S6. Preparation of active ingredients of water phase and oil phase:

[0055] Prepare an aqueous phase by dissolving sodium hyaluronate and water-soluble components of tea polyphenols in deionized water;

[0056] preparing an oil phase by uniformly mixing vitamin E and squalane-based oil-soluble components to obtain an oil phase;

[0057] S7. Design and loading of layered storage system: the plant fiber composite carrier, water phase and oil phase are sequentially loaded into the container in layers, and a double-layer diaphragm is provided in the container to isolate the components of each layer;

[0058] S8. Product sealing and storage: Seal the filled container and store it.

[0059] The pretreatment of the carbon material in step S1 includes mixing the carbon material with a 0.02 mol / L 3-aminopropyltriethoxysilane solution and stirring the mixture in a 60° C. water bath for 1-3 hours.

[0060] The steps for preparing the molecularly imprinted carbon material in step S2 include:

[0061] The template molecule is vitamin C, with a concentration of 0.01-0.1 mol / L;

[0062] The monomer is methyl methacrylate, with a concentration of 0.1-0.5 mol / L;

[0063] The cross-linking agent is ethylene glycol dimethacrylate, with a concentration of 0.05-0.2 mol / L;

[0064] The polymerization reaction was carried out at 50-70°C for 2-4h under nitrogen protection.

[0065] The step of removing the template molecules in step S3 includes washing alternately with ethanol and deionized water assisted by ultrasonic wave, each washing lasts 5-10 minutes, and a total of three washings.

[0066] In step S4, the plant fiber is seaweed fiber, and its concentration is 0.5-2% w / v. The porous network structure is formed by adjusting the pH of the solution to 6-7 and stirring at 30-50° C. for 0.5-2 h.

[0067] The preparation of the plant fiber composite carrier in step S5 includes adding the molecular imprinted carbon material into the seaweed fiber solution, adding calcium chloride as a cross-linking agent at a concentration of 0.01-0.05 mol / L, and reacting at 20-25° C. for 20-40 minutes.

[0068] The tiered storage system in step S7 includes three layers:

[0069] The first layer is the aqueous phase, which contains sodium hyaluronate and tea polyphenols in a concentration range of 0.01-0.1% w / v;

[0070] The second layer is the oil phase, which contains vitamin E and squalane in a concentration range of 0.05-0.5% w / v;

[0071] The third layer is a carbon material / plant fiber composite phase, the carbon material concentration is 0.1-1% w / v, and the plant fiber concentration is 0.5-2% w / v.

[0072] The thickness of the double-layer membrane in the container in step S7 is 0.1-0.5 mm.

[0073] The specific steps of preparing the aqueous phase in step S6 include:

[0074] Dissolve sodium hyaluronate and tea polyphenols in deionized water, and control the initial temperature of the water at 20-30°C;

[0075] The concentration of sodium hyaluronate is 0.05-0.2% w / v, and the concentration of tea polyphenols is 0.01-0.1% w / v;

[0076] A magnetic stirrer is used during the dissolution process, with a stirring speed of 200-500 rpm and a stirring time of 15-30 min until the sodium hyaluronate is completely dissolved;

[0077] After adding tea polyphenols to the sodium hyaluronate solution, continue stirring for 5-15 minutes to make it evenly dispersed and dissolved;

[0078] The pH value of the solution can be adjusted to 5.0-6.5.

[0079] The specific steps of preparing the oil phase in step S6 include:

[0080] In a clean container, vitamin E and squalane are uniformly mixed, wherein the concentration of vitamin E is 0.1-0.3% w / v, and the concentration of squalane is 0.05-0.2% w / v;

[0081] Use a stirrer to stir at a speed of 150-300 rpm for 15-30 min to fully dissolve the vitamin E and squalane to form a uniform oil phase;

[0082] If necessary, the temperature can be raised to 30-50°C to accelerate dissolution, and avoid light during stirring.

[0083] Example 1: Preparation of high concentration molecularly imprinted carbon materials

[0084] Technical steps:

[0085] S1. Pretreatment of carbon materials:

[0086] The carbon material was crushed to a particle size of 10 nm and mixed with 0.02 mol / L 3-aminopropyltriethoxysilane solution.

[0087] The mixture was stirred in a water bath at 60°C for 3 hours.

[0088] S2. Preparation of molecularly imprinted carbon materials:

[0089] The template molecule is vitamin C with a concentration of 0.1 mol / L; the monomer is methyl methacrylate (MMA) with a concentration of 0.5 mol / L; and the cross-linking agent is ethylene glycol dimethacrylate (EGDMA) with a concentration of 0.2 mol / L.

[0090] The copolymerization reaction was carried out at 50°C for 4 hours under nitrogen protection.

[0091] S3. Template molecule removal:

[0092] Using a 0.22 μm filter membrane, ultrasonic-assisted washing was performed with ethanol and deionized water, respectively, for 10 min each time, for a total of three washes.

[0093] S4. Preparation of plant fiber network structure:

[0094] Alginate fiber with a concentration of 2% (w / v) was dissolved in deionized water, and the pH of the solution was adjusted to 6.5.

[0095] The mixture was stirred at 30 °C for 1 hour to form a three-dimensional porous structure.

[0096] S5. Preparation of plant fiber composite carrier:

[0097] The molecularly imprinted carbon material was added into the seaweed fiber solution, and calcium chloride was added as a cross-linking agent at a concentration of 0.05 mol / L.

[0098] The reaction was carried out at 25°C for 40 minutes.

[0099] S6. Preparation of active ingredients of water phase and oil phase:

[0100] Aqueous phase: 0.2% (w / v) sodium hyaluronate and 0.1% (w / v) tea polyphenols were dissolved in deionized water, and the temperature was controlled at 30° C. The stirring speed was 500 rpm, the stirring time was 30 minutes, and the pH value was adjusted to 6.0.

[0101] Oil phase: Mix 0.3% (w / v) vitamin E and 0.2% (w / v) squalane. Stir at 300 rpm for 30 minutes, control the temperature at 50°C, and operate in a dark environment.

[0102] S7. Design and filling of tiered storage system:

[0103] The first layer is a water phase, the second layer is an oil phase, and the third layer is a carbon material / plant fiber composite phase. The concentration of the carbon material is 1% (w / v), and the concentration of the plant fiber is 2% (w / v).

[0104] The thickness of the double-layer diaphragm is 0.5 mm.

[0105] S8. Product sealing and storage:

[0106] Store in sealed container away from light.

[0107] Summarize:

[0108] This embodiment maximizes the functional properties of each layer of ingredients by increasing the concentration of molecular imprinted carbon materials, plant fiber composite carriers, water phase and oil phase ingredients. This solution is suitable for high-end skin care products, can provide high-intensity moisturizing and anti-oxidation functions, and is suitable for user groups with high requirements for product performance.

[0109] By increasing the concentration of molecularly imprinted carbon material (the vitamin C concentration was 0.1 mol / L, and the monomer and cross-linker concentrations were also high), the adsorption performance of the carbon material was enhanced, enabling it to more effectively capture and slowly release the active ingredients.

[0110] The concentration of plant fibers was increased to 2% (w / v), which enhanced the stability of the composite carrier through the three-dimensional porous structure and ensured the uniform dispersion of the carbon material.

[0111] High concentrations of sodium hyaluronate (0.2%) and tea polyphenols (0.1%) enhance the moisturizing and antioxidant effects of the water phase, while 0.3% vitamin E and 0.2% squalane in the oil phase improve moisturizing properties.

[0112] Applicable scenarios: This process is suitable for occasions with high requirements for product efficacy, especially the high-end skin care market, and can be used for consumers with functional requirements such as anti-aging, deep moisturizing and high antioxidant. The disadvantage of this embodiment is that the cost is relatively high, and it is suitable for mass production of high-end products.

[0113] Example 2: Optimization of medium-concentration composite carrier and layered storage system

[0114] Technical steps:

[0115] S1. Pretreatment of carbon materials:

[0116] The carbon material was crushed to a particle size of 20 nm, mixed with 0.02 mol / L 3-aminopropyltriethoxysilane solution, and stirred in a 60° C. water bath for 2 hours.

[0117] S2. Preparation of molecularly imprinted carbon materials:

[0118] The template molecule is vitamin C with a concentration of 0.05 mol / L; the monomer is MMA with a concentration of 0.3 mol / L; and the cross-linking agent is EGDMA with a concentration of 0.1 mol / L.

[0119] The reaction was carried out at 60°C for 3 hours under nitrogen protection.

[0120] S3. Template molecule removal:

[0121] Using a 0.22 μm filter membrane, wash the membrane with ethanol and deionized water alternately with ultrasonic assisted washing for 8 minutes each time, for a total of three times.

[0122] S4. Preparation of plant fiber network structure:

[0123] A 1% (w / v) alginate fiber solution was used, the pH was adjusted to 6.0, the temperature was controlled at 40° C., and the stirring time was 1 hour.

[0124] S5. Preparation of plant fiber composite carrier:

[0125] The molecularly imprinted carbon material was added to the seaweed fiber solution, and 0.03 mol / L calcium chloride was added, and the mixture was reacted at 22°C for 30 minutes.

[0126] S6. Preparation of active ingredients of water phase and oil phase:

[0127] Aqueous phase: Dissolve 0.1% (w / v) sodium hyaluronate and 0.05% (w / v) tea polyphenols, control the temperature at 25°C, stir at 300 rpm, stir for 20 minutes, and adjust the pH to 5.5.

[0128] Oil phase: Mix 0.2% (w / v) vitamin E and 0.1% (w / v) squalane, stir at 200 rpm for 20 minutes, and control the temperature at 40°C.

[0129] S7. Design and filling of layered storage system:

[0130] The first layer is a water phase, the second layer is an oil phase, and the third layer is a carbon material / plant fiber composite phase. The concentration of the carbon material is 0.5% (w / v), and the concentration of the plant fiber is 1% (w / v).

[0131] The thickness of the double-layer diaphragm is 0.3 mm.

[0132] S8. Product sealing and storage:

[0133] Seal the container and store in a refrigerator at 4°C.

[0134] Summarize:

[0135] Example 2 is designed in a balanced way in terms of component concentration, stirring time, temperature control, etc., to ensure that the prepared composite carrier and the aqueous phase and oil phase components are balanced between cost and performance. This solution is suitable for the general skin care product market, has both stability and moderate cost, and is suitable for medium-priced skin care products.

[0136] In the molecularly imprinted carbon material, the concentration of vitamin C is set to 0.05 mol / L, and the concentrations of the monomer and cross-linker are 0.3 mol / L and 0.1 mol / L. This moderate concentration can provide good adsorption capacity while reducing material consumption.

[0137] The plant fiber concentration is 1% (w / v), and the moderate fiber network structure provides a stable sustained-release function, reduces the risk of precipitation, and improves the uniformity of the product.

[0138] The concentrations of water phase and oil phase ingredients are in the range of 0.1% and 0.2% respectively. Moderate concentrations can meet daily moisturizing and anti-oxidation needs and are more cost-effective.

[0139] Applicable scenarios: This embodiment is suitable for mass production of general skin care products, and is suitable for daily skin care products that pursue balance, such as basic moisturizing essence or antioxidant essence. This solution reduces production costs while ensuring skin care efficacy, and is suitable for daily use by general consumers.

[0140] Example 3: Low concentration and low temperature preparation process

[0141] Technical steps:

[0142] S1. Pretreatment of carbon materials:

[0143] The carbon material was crushed to a particle size of 50 nm, mixed with 0.02 mol / L 3-aminopropyltriethoxysilane solution, and stirred in a 60° C. water bath for 1 hour.

[0144] S2. Preparation of molecularly imprinted carbon materials:

[0145] The template molecule is vitamin C with a concentration of 0.01 mol / L; the monomer is MMA with a concentration of 0.1 mol / L; and the cross-linking agent is EGDMA with a concentration of 0.05 mol / L.

[0146] The polymerization reaction was carried out at 50°C for 2 hours under nitrogen protection.

[0147] S3. Template molecule removal:

[0148] Using a 0.45 μm filter membrane, ultrasonic-assisted washing was performed with ethanol and deionized water, three times for 5 min each.

[0149] S4. Preparation of plant fiber network structure:

[0150] A 0.5% (w / v) alginate fiber solution was used, the pH was adjusted to 7.0, the temperature was controlled at 30° C., and the stirring time was 0.5 hours.

[0151] S5. Preparation of plant fiber composite carrier:

[0152] The molecularly imprinted carbon material was added to the seaweed fiber solution, and 0.01 mol / L calcium chloride was added, and the mixture was reacted at 20°C for 20 minutes.

[0153] S6. Preparation of active ingredients of water phase and oil phase:

[0154] Aqueous phase: Dissolve 0.05% (w / v) sodium hyaluronate and 0.01% (w / v) tea polyphenols at 20°C and 200 rpm for 15 minutes, and adjust the pH to 5.0.

[0155] Oil phase: Mix 0.1% (w / v) vitamin E and 0.05% (w / v) squalane, stir at 150 rpm for 15 minutes, and control the temperature at 30°C.

[0156] S7. Design and filling of tiered storage system:

[0157] The first layer is a water phase, the second layer is an oil phase, and the third layer is a carbon material / plant fiber composite phase. The concentration of the carbon material is 0.1% (w / v), and the concentration of the plant fiber is 0.5% (w / v).

[0158] The thickness of the double-layer diaphragm is 0.1 mm.

[0159] S8. Product sealing and storage:

[0160] Store in sealed container at room temperature away from light.

[0161] Summarize:

[0162] Example 3 uses lower concentration ingredients and a low temperature preparation process to reduce the overall cost, which is suitable for products with limited budgets or that focus on mild formulas. The low concentration ingredients of this solution are combined with mild preparation conditions, which is suitable for the entry-level skin care product market and meets the needs for low cost and mildness.

[0163] The concentrations of template molecules, monomers and cross-linking agents of molecularly imprinted carbon materials were set at 0.01 mol / L, 0.1 mol / L and 0.05 mol / L, respectively, which further reduced the amount of materials used while ensuring the basic adsorption effect.

[0164] The concentration of seaweed fiber is 0.5% (w / v). The low-concentration fiber mesh structure reduces material consumption and is suitable for basic sustained release and stable dispersion requirements.

[0165] The concentrations of the water phase and oil phase are set to 0.05% and 0.1%, achieving basic moisturizing and nourishing functions and meeting the requirements of low-concentration skin care products.

[0166] The operating temperature is controlled between 20-30°C, reducing the impact on temperature-sensitive ingredients and ensuring the stability of mild formulas.

[0167] Applicable scenarios: Suitable for entry-level or low-cost skin care market, targeting users with low budgets, such as basic moisturizing essence or daily moisturizing essence, etc. This low-concentration, low-temperature preparation process not only reduces costs, but is also suitable for the development of sensitive skin products.

[0168] Summary:

[0169] These three examples respectively demonstrate different preparation schemes from high concentration to low concentration, and from high performance to low cost. The specific summary is as follows:

[0170] Example 1 focuses on improving product performance, and is suitable for the high-end skin care product market through higher concentrations of ingredients and enhanced adsorption and sustained release effects. Its advantage is strong functionality, and its disadvantage is relatively high cost.

[0171] Example 2 achieves a balance between cost and performance and is suitable for the daily skin care product market. This example combines moderate concentration and reasonable preparation conditions, achieves a good balance between skin care efficacy and cost, and is suitable for the daily skin care needs of general consumers.

[0172] Example 3 focuses on the development of low-cost and mild formulas, and is suitable for entry-level skin care products or low-cost markets through low concentration and low-temperature preparation conditions. This example has a low cost and meets the mildness requirements, and is suitable for users with limited budgets or for sensitive skin products.

[0173] Summary:

[0174] These three examples demonstrate different improvements in the charcoal essence preparation process:

[0175] In the high-end skin care market, the highly concentrated and highly active Example 1 provides excellent skin care effects and is suitable for users who seek high performance;

[0176] In the daily skin care product market, Example 2 provides users with reliable daily skin care products by balancing ingredient concentrations and process conditions;

[0177] In the entry-level or sensitive skin market, Example 3 provides a gentle and effective skin care option for budget-conscious users through a low-concentration, low-cost process.

[0178] Each embodiment makes full use of the innovative process of the present invention and provides differentiated product solutions in combination with different market demands. These solutions demonstrate the flexibility and adaptability of the present invention in terms of ingredient selection, concentration adjustment, process optimization, etc., and can provide customized solutions for different skin care needs.

[0179] Experimental plan: Comprehensive performance test of charcoal essence

[0180] Experiment 1: Adsorption performance test of molecularly imprinted carbon materials

[0181] Purpose:

[0182] The specific adsorption performance of molecularly imprinted carbon materials for vitamin C was evaluated, the adsorption effects under different temperature and time conditions were analyzed, and the adsorption effects of molecularly imprinted carbon materials and non-imprinted carbon materials were compared.

[0183] Experimental design:

[0184] Temperature control: The experiments were carried out in groups at 25℃ (room temperature) and 37℃ (simulated human body temperature).

[0185] Time control: Three time points of 3 hours, 6 hours and 12 hours were set for each group of samples to observe the changes of adsorption over time.

[0186] Control experiment: Set up a control group (non-imprinted carbon material) and compare it with the experimental group to verify the advantages of molecularly imprinted carbon materials.

[0187] Experimental materials and equipment:

[0188] Materials: molecularly imprinted carbon material samples (Example 1, Example 2, Example 3), control group (non-imprinted carbon material), vitamin C solution (0.05 mol / L)

[0189] Equipment: High performance liquid chromatography (HPLC), constant temperature water bath, electronic balance, magnetic stirrer, centrifuge, glass beaker, measuring cylinder, 0.22 μm filter membrane

[0190] Experimental steps:

[0191] To prepare the vitamin C solution:

[0192] Accurately weigh vitamin C, use deionized water to prepare a 0.05 mol / L vitamin C solution, and mix well.

[0193] The solution was filtered using a 0.22 μm filter membrane to remove possible particulate impurities and ensure the purity of the solution.

[0194] Weigh the molecularly imprinted carbon material:

[0195] Accurately weigh 50 mg of molecularly imprinted carbon material sample and put it into different glass beakers.

[0196] Each sample was divided into two temperature groups (25°C and 37°C), and each temperature group was further divided into three adsorption time periods (3 hours, 6 hours, and 12 hours).

[0197] Add Vitamin C solution:

[0198] 10 mL of vitamin C solution was added into each beaker to allow the molecularly imprinted carbon material to fully contact with the solution.

[0199] Control temperature and adsorption time:

[0200] The samples were placed in a constant temperature water bath at 25°C and 37°C, respectively.

[0201] Samples were taken at each time point (3 h, 6 h, and 12 h), and stirring was performed with a magnetic stirrer for 1 min every 30 min to ensure that the carbon material was in full contact with the solution.

[0202] Filtration and determination:

[0203] After each adsorption time, the solution was filtered with a 0.22 μm filter membrane and part of the solution was transferred to a sample bottle.

[0204] The residual concentration of vitamin C in the filtrate was detected by HPLC. The residual concentration of each sample was recorded and the adsorption amount (mg / g) was calculated.

[0205] Calculate the adsorption amount:

[0206] The adsorption amount was calculated according to the following formula:

[0207]

[0208] Where C0 is the initial concentration, C is the residual concentration, V is the volume of the solution, and m is the mass of the carbon material.

[0209] Table 1:

[0210]

[0211] Experimental summary:

[0212] The adsorption performance is significantly improved: The experimental data show that the molecular imprinted carbon material of Example 1 has the highest adsorption capacity at 25°C and 37°C, especially at 37°C for 6 hours, reaching 29.5 mg / g, which is much higher than the control group (7.5 mg / g) and the non-imprinted carbon material (5.0 mg / g). This shows that the molecular imprinted structure of the present invention significantly improves the adsorption capacity of vitamin C.

[0213] Temperature effect: At 37°C, the adsorption amount of Example 1 is significantly higher than that at 25°C, indicating that the increase in temperature helps to accelerate the adsorption process and make the adsorption effect of the molecularly imprinted carbon material more significant.

[0214] Best adsorption material: Example 1 exhibits the best adsorption performance under all conditions, indicating that its molecular imprinting structure is the most perfect and is suitable for use in the preparation of essences requiring high-efficiency adsorption.

[0215] Experiment 2: Sustained release performance test

[0216] Purpose:

[0217] The sustained-release properties of the charcoal essence samples at simulated skin temperature (37°C) were evaluated, and the release of active ingredients in different time periods was analyzed by continuous sampling.

[0218] Experimental design:

[0219] Time Segmentation: Set sampling time periods of 4, 8, 12 and 24 hours to measure the sustained release of active ingredients.

[0220] Dynamic environment: Replace the buffer every 4 hours to simulate the skin contact environment, maintain the concentration gradient, and ensure continuous release.

[0221] Experimental materials and equipment:

[0222] Materials: Charcoal essence samples (Example 1, Example 2, Example 3 and control group), buffer solution (pH 5.5, simulating skin pH)

[0223] Equipment: Constant temperature water bath (37°C), HPLC, sampler, centrifuge, 0.22 μm filter membrane, test tube, pipette, beaker

[0224] Experimental steps:

[0225] Buffer preparation:

[0226] Prepare a buffer solution with pH 5.5 to simulate the skin environment. Place the buffer solution in a constant temperature water bath and maintain it at 37°C.

[0227] Sample processing:

[0228] Take 10 mL of the charcoal essence sample and place it in 10 mL of buffer, making sure the sample is completely immersed.

[0229] Time sampling and dynamic replacement:

[0230] Every 4 hours, 0.5 mL of buffer was drawn out with a pipette as a sample and supplemented with 0.5 mL of fresh buffer to maintain the solution concentration gradient.

[0231] The sampling times were 4 hours, 8 hours, 12 hours and 24 hours.

[0232] Sample separation and detection:

[0233] After each sampling, the sample was centrifuged and filtered through a 0.22 μm filter membrane.

[0234] The concentration of active ingredient in the filtrate was detected by HPLC, and the release amount at each time point was recorded.

[0235] Table 2:

[0236]

[0237] Experimental summary:

[0238] The sustained-release performance is significantly improved: the cumulative release amount of Example 1 within 24 hours is 19.5 mg / L, which is significantly higher than 10.0 mg / L of the control group, proving that the molecularly imprinted carbon material of the present invention can achieve a longer and more stable sustained-release effect.

[0239] Gradual release of active ingredients: The sustained release curves of Examples 1, 2 and 3 are smooth and the release rate is slow, gradually releasing the active ingredients, while the control group exhibits the characteristics of rapid release, with a fast release rate but a short duration.

[0240] Best sustained-release material: The sustained-release effect of Example 1 is the most significant, and is suitable for use in the preparation of essences that require long-lasting skin care effects. It can continuously release active ingredients within 24 hours, helping to achieve long-lasting skin care effects.

[0241] Experiment 3: Stability test

[0242] Purpose:

[0243] The stability of the charcoal essence was tested under different temperature and humidity conditions, and its chemical and physical stability during long-term storage was analyzed.

[0244] Experimental design:

[0245] Temperature grouping: The samples were stored at 40℃, 25℃ and 4℃ respectively to simulate high temperature, room temperature and refrigerated environment.

[0246] Humidity grouping: Tests were conducted at 40% and 75% humidity to observe the effect of humidity on stability.

[0247] Regular sampling: Samples are collected every 10 days to detect changes in active ingredient concentration and physical appearance.

[0248] Experimental materials and equipment

[0249] Materials: Charcoal essence samples (Example 1, Example 2, Example 3 and control group)

[0250] Equipment: Constant temperature and humidity chamber (40℃ / 75%, 25℃ / 40%, 4℃ / 40%), HPLC, 0.22μm filter membrane

[0251] Experimental steps:

[0252] Sample packaging:

[0253] The charcoal essence samples were divided into several sealed sterile test tubes and placed in a constant temperature and humidity chamber under different conditions (40°C / 75%, 25°C / 40%, 4°C / 40%).

[0254] Regular sampling:

[0255] Take out samples every 10 days and observe their appearance (such as whether there is stratification or precipitation).

[0256] The concentration of active ingredients was determined using HPLC and the data were recorded in a table.

[0257] Table 3:

[0258]

[0259]

[0260] Experimental summary:

[0261] Excellent high temperature stability: Under the conditions of 40°C and 75% humidity, the samples of Examples 1, 2, and 3 maintained a high concentration of active ingredients within 30 days without stratification, while the control group showed obvious stratification and concentration decrease under high temperature and high humidity, indicating that the charcoal essence of the present invention has better stability under high temperature environment.

[0262] Environmental tolerance: Under refrigerated conditions at 4°C, all samples maintained their initial concentrations within 30 days, especially Example 1, which was suitable for storage under various environmental conditions, thus extending the shelf life of the product.

[0263] Recommended applicable environment: The charcoal essence of the present invention exhibits good chemical and physical stability at both room temperature and low temperature environments, and is suitable for use under different climatic conditions.

[0264] Experiment 4: Moisturizing performance test

[0265] Purpose:

[0266] The charcoal serum was applied to the subjects' skin and the changes in skin moisture content were detected to evaluate its long-term moisturizing effect.

[0267] Experimental design:

[0268] Time segment: Set 0 hours, 4 hours, 8 hours and 24 hours time periods to observe the skin moisture retention rate.

[0269] Control group comparison: compared with the control group samples, the moisturizing effect of the molecularly imprinted carbon material was verified.

[0270] Experimental materials and equipment:

[0271] Materials: Charcoal essence samples (Example 1, Example 2, Example 3 and control group)

[0272] Equipment: Skin moisture tester, measuring cup, timer, 10 subjects

[0273] Experimental steps:

[0274] Subject preparation:

[0275] Make sure the subject's arms are clean and dry, apply different charcoal serum samples on the arm area and mark different locations.

[0276] Initial Measurement:

[0277] Immediately after applying the charcoal serum, the initial skin moisture content (0 hour) was measured using a skin moisture tester.

[0278] Subsequent measurements:

[0279] Skin moisture content was measured after 4 hours, 8 hours and 24 hours, and the data were recorded.

[0280] Table 4:

[0281]

[0282] Experimental summary:

[0283] Long-lasting moisturizing effect is significant: after 24 hours, the skin moisture retention rate of Example 1 is the highest, reaching 55.0%, which is much higher than 44.0% of the control group. This shows that the charcoal essence of the present invention can provide a more lasting moisturizing effect.

[0284] Advantages of molecular imprinted structure: The moisture retention rates of Examples 1, 2 and 3 are better than those of the control group, showing the significant advantages of molecular imprinted carbon materials in water locking and moisturizing, especially Example 1 has the most outstanding effect.

[0285] Suitable for long-term skin care needs: Experimental results show that the charcoal essence of the present invention can maintain high skin moisture within 24 hours, is suitable for use in skin care products that require long-term moisturizing, and helps to improve the skin's water retention capacity.

[0286] Summary:

[0287] Based on the results of the four experiments, the charcoal essence of the present invention is superior to the control group in terms of adsorption performance, sustained release performance, stability and moisturizing performance, which are summarized as follows:

[0288] Improved adsorption performance: Through the design of molecular imprinting structure, the carbon essence of the present invention shows stronger adsorption capacity for active ingredients (such as vitamin C), especially under high temperature and long time conditions, the adsorption amount far exceeds that of the control group. The molecular imprinting structure effectively enhances the specific adsorption capacity of the carbon material, giving it a significant advantage in adsorbing skin care active ingredients.

[0289] Long-lasting sustained-release effect: The charcoal essence of the present invention can stably release the active ingredients within 24 hours and gradually penetrate into the skin, avoiding the problem of concentration drop after rapid release in the control group. This long-lasting sustained-release property makes it suitable for products with continuous skin care needs, extending the effective action time of the active ingredients.

[0290] Excellent environmental stability: The charcoal essence of the present invention showed good stability under different temperature and humidity conditions, especially under high temperature and high humidity conditions, and was able to maintain a high concentration of active ingredients and physical stability. In comparison, the control group showed stratification under high temperature conditions, and the concentration of active ingredients also decreased significantly, showing the applicability of the present invention in a variety of environments.

[0291] Significant moisturizing effect: In the 24-hour moisturizing test, the moisture retention rate of Example 1 reached 55.0%, which was much higher than 44.0% of the control group, proving that the charcoal essence of the present invention can significantly increase the moisture content of the skin and provide a long-lasting moisturizing effect. This makes the product of the present invention suitable for skin care occasions that require long-lasting moisturizing and deep nourishment, helping to improve dry skin problems.

[0292] in conclusion:

[0293] The four tests of this experimental scheme fully verified the performance advantages of the carbon essence of the present invention, proving its superior comprehensive performance in adsorption, sustained release, stability and moisturizing. Compared with the prior art, the molecularly imprinted carbon material of the present invention significantly improves the functionality and applicability of the product, and is suitable for a variety of skin care needs such as long-term skin care, anti-oxidation, and moisturizing. This technological innovation provides a new type of functional material for the skin care industry, which has broad application prospects.

[0294] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a carbon essence, characterized in that: The following steps are involved: S1. Pretreatment of carbon materials: crushing the carbon materials to a particle size of 10-50 nm, and surface treating the carbon materials with a surface modifier to form active sites on the surface of the carbon materials; S2. Preparation of molecularly imprinted carbon material: mixing the pre-treated carbon material with the template molecule, the monomer and the cross-linking agent, and performing copolymerization on the surface of the carbon material to form a molecularly imprinted structure; S3, after the reaction is completed, the template molecules are removed using a washing solvent to obtain a molecularly imprinted carbon material; S4. Preparation of plant fiber network structure: dissolving or dispersing plant fibers in water, and preparing a three-dimensional porous network structure by adjusting the pH value and controlling the stirring temperature and time; S5. Preparation of plant fiber composite carrier: cross-linking the molecularly imprinted carbon material with the plant fiber network structure to obtain the plant fiber composite carrier; S6. Preparation of active ingredients of water phase and oil phase: Prepare an aqueous phase by dissolving sodium hyaluronate and water-soluble components of tea polyphenols in deionized water; preparing an oil phase by uniformly mixing vitamin E and squalane-based oil-soluble components to obtain an oil phase; S7. Design and loading of layered storage system: the plant fiber composite carrier, water phase and oil phase are sequentially loaded into the container in layers, and a double-layer diaphragm is provided in the container to isolate the components of each layer; S8. Product sealing and storage: Seal the filled container and store it.

2. The process for preparing a carbon essence according to claim 1, characterized in that: The pretreatment of the carbon material in step S1 comprises mixing the carbon material with a 0.02 mol / L 3-aminopropyltriethoxysilane solution and stirring the mixture in a 60° C. water bath for 1-3 hours.

3. The process for preparing a carbon essence according to claim 1, characterized in that: The steps of preparing the molecularly imprinted carbon material in step S2 include: The template molecule is vitamin C, with a concentration of 0.01-0.1 mol / L; The monomer is methyl methacrylate, and the concentration is 0.1-0.5 mol / L; The cross-linking agent is ethylene glycol dimethacrylate, and the concentration is 0.05-0.2 mol / L; The polymerization reaction was carried out at 50-70°C for 2-4h under nitrogen protection.

4. The process for preparing a carbon essence according to claim 1, characterized in that: The step of removing the template molecules in step S3 includes washing alternately with ethanol and deionized water assisted by ultrasonic wave, each washing lasts 5-10 minutes, and a total of three washings.

5. The process for preparing a carbon essence according to claim 1, characterized in that: In the step S4, the plant fiber is seaweed fiber with a concentration of 0.5-2% w / v, and a porous network structure is formed by adjusting the pH of the solution to 6-7 and stirring at 30-50° C. for 0.5-2 h.

6. The process for preparing a carbon essence according to claim 1, characterized in that: The preparation of the plant fiber composite carrier in step S5 includes adding the molecularly imprinted carbon material into the seaweed fiber solution, adding calcium chloride as a cross-linking agent at a concentration of 0.01-0.05 mol / L, and reacting at 20-25° C. for 20-40 minutes.

7. The process for preparing a carbon essence according to claim 1, characterized in that: The hierarchical storage system in step S7 includes a three-layer structure, namely: The first layer is the aqueous phase, which contains sodium hyaluronate and tea polyphenols in a concentration range of 0.01-0.1% w / v; The second layer is the oil phase, which contains vitamin E and squalane in a concentration range of 0.05-0.5% w / v; The third layer is a carbon material / plant fiber composite phase, the carbon material concentration is 0.1-1% w / v, and the plant fiber concentration is 0.5-2% w / v.

8. The process for preparing a carbon essence according to claim 1, characterized in that: In the step S7, the thickness of the double-layer diaphragm in the container is 0.1-0.5 mm.

9. The process for preparing a carbon essence according to claim 1, characterized in that: The specific steps of preparing the aqueous phase in step S6 include: Dissolve sodium hyaluronate and tea polyphenols in deionized water, and control the initial temperature of the water at 20-30°C; The concentration of sodium hyaluronate is 0.05-0.2% w / v, and the concentration of tea polyphenols is 0.01-0.1% w / v; A magnetic stirrer is used during the dissolution process, with a stirring speed of 200-500 rpm and a stirring time of 15-30 min until the sodium hyaluronate is completely dissolved; After adding tea polyphenols to the sodium hyaluronate solution, continue stirring for 5-15 minutes to make it evenly dispersed and dissolved; The pH value of the solution can be adjusted to 5.0-6.

5.

10. The process for preparing a carbon essence according to claim 1, characterized in that: The specific steps of preparing the oil phase in step S6 include: In a clean container, vitamin E and squalane are uniformly mixed, wherein the concentration of vitamin E is 0.1-0.3% w / v, and the concentration of squalane is 0.05-0.2% w / v; Use a stirrer to stir at a speed of 150-300 rpm for 15-30 min to fully dissolve the vitamin E and squalane to form a uniform oil phase; If necessary, the temperature can be raised to 30-50°C to accelerate dissolution, and avoid light during stirring.